Broadband Back-Short Transition From Waveguide to Thin Substrate-Integrated Waveguide in Multilayer Substrate in 270-GHz Band - Shumpei Kishi; Yoshiki Sugimoto; Kunio Sakakibara; Nobuyoshi Kikuma (IEEE Journal of Microwaves)
A broadband right-angle transition from a rectangular waveguide (RWG) to a substrate-integrated waveguide (SIW) with a small narrow-wall width is proposed in the 270 GHz band. Generally, it is difficult to design a broadband transition from a standard RWG to an SIW with a small narrow-wall width owing to the small characteristic impedance of the SIW. In this study, wideband characteristics are obtained by placing via holes in a multilayer substrate and forming back-short structures, short stubs, and inductive pins. By varying the positions of the via holes, the two resonant frequencies are independently controlled to achieve a broad bandwidth exceeding 26%. To verify this design, back-to-back DUTs (devices under test) were fabricated and measured in the sub-terahertz band. The measured and simulated results are in good agreement. The measured insertion loss is approximately 1.1 dB at a design frequency of 275 GHz, and the measured reflection loss is less than −10 dB from 234 GHz to 308 GHz.